Cyathea tenggerensis (Rosenst.) Domin from Ijen Geopark, Bondowoso and Banyuwangi, East Java - Ulum Fuad Bahrul; Su’udi Mukhamad; Dwinanti Edia Fitri; Fernanda Rachel Oktavian; Setyati Dwi (BIO Web of Conferences)
Cyathea contaminans (Hook.) Copel. and Cyathea orientalis (Kunze) T. Moore, which flourish abundantly in the Erek-erek Geoforest ecotourism zone within Ijen Geopark, have long been regarded as ancient plant species. However, during a recent expedition to higher elevations, a tree fern with distinct morphological features, previously unreported, was discovered. The study, conducted in June 2024 within Ijen Geopark, encompassing the Bondowoso and Banyuwangi Regencies of East Java, involved the documentation and morphological observation of tree ferns at the site. The specimen identified was Cyathea tenggerensis (Rosenst.) Domin, a species distinguished by its unique characteristics, including dense golden-brown hairs enveloping throughout the stipe and costae, a height of up to 10 metres, and a trunk diameter significantly greater than that of C. contaminans and C. orientalis. As no prior records of this species exist within the conservation area, this study provides the first insight into its distribution. Furthermore, the research presents a detailed description of C. tenggerensis and identifies key morphological traits critical for accurate field identification. In light of these findings, we advocate for enhanced conservation measures to safeguard the long-term survival of tree ferns within their native habitat.